2021
DOI: 10.1101/2021.06.01.21258155
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effects of Acute Normovolemic Hemodilution on Post-Cardiopulmonary Bypass Coagulation Tests and Allogeneic Blood Transfusion in Thoracic Aortic Repair Surgery: An Observational Cohort Study

Abstract: Background and Aim: Perioperative blood transfusion is associated with increased morbidity and mortality. Acute normovolemic hemodilution (ANH) is a blood conservation strategy associated with variable success, and rarely studied in more complex cardiac procedures. The study aim was to evaluate whether acute ANH improves coagulopathy and reduces blood transfusions in thoracic aortic surgeries. Methods: Single-center observational cohort study comparing ANH and standard institutional practice in patients wh… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Of note, some studies have also demonstrated a reduction in transfusion 20,21 . Indeed, some studies demonstrate that transfusion cannot be reduced 8,22 . In our study, the discrepancy might have occurred for the following reasons.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…Of note, some studies have also demonstrated a reduction in transfusion 20,21 . Indeed, some studies demonstrate that transfusion cannot be reduced 8,22 . In our study, the discrepancy might have occurred for the following reasons.…”
Section: Discussionmentioning
confidence: 55%
“…However, this technique is not considered a routine treatment. Besides, under diverse circumstances, the effect of this technique remains inconsistent 7–10 . Therefore, in this randomized, single‐blind study, we evaluated if ANH could reduce allogeneic red blood cell transfusion in orthognathic surgery.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,4 However, recent studies showed ANH to be associated with reduced transfusions in complex thoracic aortic repairs. 8,16,17 Possible reasons for relative under-utilization of hemodilution in such surgeries are concerns for hemodynamic instability during and after removal of autologous blood, as well as decreased oxygen delivery during the hemodilution period. [18][19][20] Hence, rather than addressing transfusion-sparing benefits of ANH that have been studied before, we focused on assessing perturbations in laboratory, physiological parameters, and outcomes to assess safety of hemodilution in complex cardiac surgeries.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, this technique has been under‐studied in complex and higher‐risk cardiac surgeries, compared to less complex procedures such as CABG, single valve, or concomitant CABG and single valve procedures 3,4 . However, recent studies showed ANH to be associated with reduced transfusions in complex thoracic aortic repairs 8,16,17 . Possible reasons for relative under‐utilization of hemodilution in such surgeries are concerns for hemodynamic instability during and after removal of autologous blood, as well as decreased oxygen delivery during the hemodilution period 18–20 .…”
Section: Discussionmentioning
confidence: 99%